Controversial advertising of medicines. A comparison between Poland and the United States - Makowska, Marta (Annales. Etyka w Życiu Gospodarczym, 2019)
For many years, the subject of aggressive marketing campaigns conducted by pharmaceutical companies has been raised in Poland. Drug ads are everywhere, on television, the radio, magazines and on the Internet. Therefore, it is extremely important is to ensure both their legal and ethical dimension. This article will present the differences between direct-to-consumer advertising of medicines in Poland and in the US. The dissimilarities result mainly from differences in legislation. In Poland, the law is much stricter than in the US. For example, in the United States companies are allowed to advertise prescription drugs directly to patients. In the whole of the European Union, and thus in Poland, it is strictly prohibited. The article will also present other regulations existing in Poland and in the United States and it will compare them. It will offer examples of violations of the law and ethics in the advertising of medicine in both countries. Lastly, it will briefly outline the negative consequences of unacceptable pharmaceutical marketing.